2010
DOI: 10.1177/016173461003200104
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Comparison of Backscatter Coefficient Estimates for Tissue-Mimicking Phantoms

Abstract: Utrasonic backscatter is useful for characterizing tissues and several groups have reported methods for estimating backscattering properties. Previous interlaboratory comparisons have been made to test the ability to accurately estimate the backscatter coefficient (BSC) by different laboratories around the world. Results of these comparisons showed variability in BSC estimates but were acquired only for a relatively narrow frequency range, and, most importantly, lacked reference to any independent predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 22 publications
2
31
0
Order By: Relevance
“…The laboratory results are from combined measurements using four single-element transducers as previously presented. 8 From Fig. 2, it can be observed that BSC estimates from all systems are in very good agreement with values from Faran's theory as well as the laboratory measurements.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The laboratory results are from combined measurements using four single-element transducers as previously presented. 8 From Fig. 2, it can be observed that BSC estimates from all systems are in very good agreement with values from Faran's theory as well as the laboratory measurements.…”
Section: Resultssupporting
confidence: 73%
“…[7][8][9] These studies have enabled researchers to uncover sources of errors in measurements that, once eliminated, resulted in inter-laboratory agreement among BSC estimates on identical samples. 8,9 The studies by Wear et al, 7 Anderson et al, 8 and King et al 9 focused on laboratory-based systems, measurement, and data processing techniques. However, to apply QUS in a clinical setting, it is necessary to also demonstrate system and operator independence of BSC estimates using arraybased ultrasound imaging systems.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations